2020
DOI: 10.31234/osf.io/dz5v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mental health outcomes of quarantine and isolation for infection prevention: A systematic umbrella review of the global evidence

Abstract: Background: Transmission of infectious diseases is often prevented by quarantine and isolation of the populations at risk. These approaches restrict the mobility, social interactions, and daily activities of the affected individuals. In recent novel coronavirus disease (COVID-19) pandemic, quarantine and isolation are being adopted in many contexts, which necessitates an evaluation of global evidence on how such measures impact the mental health outcomes among populations. This umbrella review aimed to synthes… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(15 citation statements)
references
References 23 publications
0
13
0
2
Order By: Relevance
“…Previous research suggested that emotional stressors and existential stressors due to financial concerns range among the major stressors’ psychotherapists are exposed to ( Petrowski et al, 2014 ; Puig et al, 2014 ). The novel coronavirus disease (COVID-19) and the measures necessary to fight it (i.e., quarantine, isolation, and social distancing; see Nussbaumer-Streit et al, 2020 ) are new stressors, which can increase and even cause public mental health problems ( Brooks et al, 2020 ; Hossain et al, 2020 ; Sharma et al, 2020 ). Mental health care is, therefore, essential during and after COVID-19 ( Fiorillo and Gorwood, 2020 ; Pfefferbaum and North, 2020 ; Xiang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research suggested that emotional stressors and existential stressors due to financial concerns range among the major stressors’ psychotherapists are exposed to ( Petrowski et al, 2014 ; Puig et al, 2014 ). The novel coronavirus disease (COVID-19) and the measures necessary to fight it (i.e., quarantine, isolation, and social distancing; see Nussbaumer-Streit et al, 2020 ) are new stressors, which can increase and even cause public mental health problems ( Brooks et al, 2020 ; Hossain et al, 2020 ; Sharma et al, 2020 ). Mental health care is, therefore, essential during and after COVID-19 ( Fiorillo and Gorwood, 2020 ; Pfefferbaum and North, 2020 ; Xiang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Historically quarantine has been related to anxiety, depression, panic, irritability, somatic disorder, and insomnia [6][7][8] . Moreover, a high level of stress and trauma-related disorders are byproducts of being isolated 5,9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…However, to the best of our knowledge, there is a scarcity of concrete evidence on the magnitude of sleep disorders among individuals affected by this pandemic. As there is a growing concern on mental health problems during research synthesis may play a critical role in understanding the burden of those problems addressing the same 6,19 . This scoping review aims to address this knowledge gap through systematically evaluating the current evidence on the epidemiological burden of sleep disorders, associated factors, and interventions addressing the problems.…”
Section: Introductionmentioning
confidence: 99%
“…It is understandable that people living in quarantine, isolation, or at risk of infectious disease outbreak are likely to experience psychosocial stress and adverse health outcomes, which may evoke interests in learning more about the disease 7 . However, such situations require assurance complemented by flow of correct information.…”
Section: Potential Strategies To Ensure Effective Health Communicatiomentioning
confidence: 99%